2017
DOI: 10.3906/kim-1607-35
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective and regioselective synthesis of $N$-substituted methyl 2-((azolyl)methyl)-3-arylacrylates from Baylis--Hillman acetates

Abstract: N -Substituted methyl 2-((azolyl)methyl)-3-arylacrylates were synthesized stereo-and regioselectively with one-pot reaction between Baylis-Hillman acetates and a suitable acylazole in the presence of K 2 CO 3 as a base catalyst.The targeted N -substituted azole acrylates were efficiently obtained in good yields (39%-89%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Only one of the possible geometric isomers was obtained with the method used here, we concluded that the developed reactions are also found to be stereoselective. When the preparation of N -substituted azole acrylonitriles is compared with the preparation of N -substituted azole acrylates [18], different stereoisomers have been obtained. While Z -isomers of N -substituted azole acrylonitriles in this work are obtained, E -isomers of N -substituted azole acrylates in our previously published work have been obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one of the possible geometric isomers was obtained with the method used here, we concluded that the developed reactions are also found to be stereoselective. When the preparation of N -substituted azole acrylonitriles is compared with the preparation of N -substituted azole acrylates [18], different stereoisomers have been obtained. While Z -isomers of N -substituted azole acrylonitriles in this work are obtained, E -isomers of N -substituted azole acrylates in our previously published work have been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…They were illustrated as valuable precursors for the synthesis of heterocycles and many biologically active molecules [16,17]. We recently reported the synthesis of several N -substituted azole acrylates from the reaction between Baylis-Hillman adducts and N -acylazoles with quantitative yields in one-pot reaction [18]. N -Acylazoles are very important synthetic auxiliaries in organic synthesis as they are stable crystalline compounds and offer mild reaction conditions to prepare amides [19,20], esters, thioesters [21], ketones [22,23], and heterocycles [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The isomerization of BH acetates or bromides with imidazole or triazoles provides facile access to functionalized allyl imidazoles or allyl triazoles [ 25 29 ]. This protocol allows high flexibility and rapid access to structurally diverse functionalized allyl imidazoles and triazoles.…”
Section: Introductionmentioning
confidence: 99%